KOMPETENSI SOSIAL GURU PENDIDIKAN AGAMA DAN DAMPAKNYA TERHADAP KEAKRABAN PESERTA DIDIK DI MTS INTEGRAL HIDAYATULLAH KOTA GORONTALO - Marfan Mamonto; Herson Anwar; Firman Sidik (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This research was conducted at MTs Integral Hidayatullah, Gorontalo City to examine the social competence of Religious Education teachers and its impact on student intimacy. The main problems found were teacher dominance in learning, a less conducive environment, and minimal interaction between teachers and students, as well as between students, which were caused by weak teacher social competence. This study aims to determine the level of social competence of Religious Education teachers and describe its impact on student intimacy. Theoretically, this research is expected to improve teacher social competence, and practically provide input to create better social relationships and a more enjoyable learning atmosphere. This study uses a qualitative approach with a descriptive method, which aims to understand in depth the social competence of Religious Education teachers and its impact on student intimacy at MTs Integral Hidayatullah, Gorontalo City. Data were collected through observation, in-depth interviews with teachers and students, and relevant documentation. Data analysis techniques were carried out inductively by reducing data, presenting data, and drawing conclusions to obtain a clear picture of the relationship between teacher social competence and the quality of student social interactions. The results of the study indicate that the social competence of Religious Education teachers has a significant impact on student intimacy at MTs Integral Hidayatullah, Gorontalo City. Teachers who possess good communication skills, empathy, and skills in managing social interactions are able to build closer and more respectful relationships with students. The intimacy formed between teachers and students strengthens students' sense of comfort and self-confidence, so they are more open and actively involved in learning activities. Furthermore, this positive relationship contributes to a more conducive social climate, which not only encourages good cooperation among students but also reduces the potential for social problems in the madrasah environment.